Interpretation and its impact on deducing legal rulings - a comparative fundamentalist study (Islamic Sciences Journal, 2023)
What prompted us to write this topic is the issuance of some corrupt interpretations from unqualified people in our time that show the Sharia contrary to reality. And one of the effects of these interpretations was to keep Muslims away from the essence of their religion and the seriousness of their rationality, thus preferring it and misleading others. Therefore, we must clarify the rules and regulations that scholars have established for the process of interpretation in order to show its effect in clarifying the texts and deducing the rulings, and this can only be achieved through sound interpretation. The general public is guilty of misunderstanding the texts, and as a deterrent to the enemies of Islam who specialize in these areas.
Keywords: Interpretation, deduction, legal rulings, fundamentalist sources